PEMAHAMAN KONTEKSTUAL TERHADAP NILAI KESAKSIAN WANITA DALAM AL-QUR’AN - Tasbih Tasbih (Al-Irsyad Al-Nafs : Jurnal Bimbingan dan Penyuluhan Islam)
The main issue to be answered in this paper is how is the contextual understanding of the value of women's testimony in the Qur'an? This study is a literature review analyzed descriptively qualitatively, with theological and sociological approaches. The results show that based on a contextual understanding of the verses regarding women's testimony, it can be said that the Qur'an never distinguishes between men and women. Al-Qur'an is precisely so respect and upholds the parallelism between men and women. However, if understood textually, it tends to show the opposite. Namely, women are still perceived as